(untitled) (Al-Aasar, 2025)
The convergence of Prophetic traditions (Aḥādīth) and modern science presents a compelling field of interdisciplinary research. This paper investigates several authentic Aḥādīth of Prophet Muhammad (peace be upon him) that relate to health, hygiene, disease prevention, and human development, and analyzes their harmony with contemporary scientific findings. Topics include the embryological development during the first forty days, antibacterial proteins found in fingertips, the Islamic instruction to purify vessels licked by a dog using soil, the presence of both disease and cure in the wings of a fly, and the prophetic guidance to avoid plague-infected areas. Each of these instructions, conveyed over 1400 years ago, is explored through a scientific lens, highlighting surprising correlations with discoveries in microbiology, epidemiology, and embryology. By analyzing the context and implications of these ḥadīths, the study demonstrates how Prophetic teachings reflect deep intuitive wisdom and foresight. These insights are not only spiritually profound but also carry practical benefits for modern public health and environmental cleanliness. The study concludes that the Aḥādīth of the Prophet Muhammad (PBUH) are rich with scientific relevance, affirming the potential of Islamic knowledge to contribute meaningfully to scientific discourse. This paper encourages further exploration of classical Islamic texts in light of modern scientific developments, paving the way for a more integrative approach to science and religion.